Detecting Circular Economy Strategies in the Fourth Sector: Overview of the Chilean Construction Sector as Evidence of a Sustainable Business Model - Cerdá Suárez, Luis Manuel; Espinosa-Cristia, Juan Felipe; Núñez Valdés, Karen; Núñez-Valdés, Gerson (Sustainability (Switzerland), 2023)
An essential part of the economic and social system is the existence of sustainable companies worldwide. Despite the fact that the literature has described different kinds of innovations, organizations, and models regarding this topic, there is a need to understand the dynamics that occur within the fourth sector and how strategies and practices are working. In this study, construction companies presenting sustainable projects are identified, and the way in which they serve the community, stakeholders, and consumers is analyzed. The present article presents an epistemological search to recognize the best practices and strategies, which allows an understanding of the new circular economy strategies in the fourth sector. The authors show a conceptual approach regarding these actions and a methodology on the most notable techniques of the Circular Economic Strategy of Chile based on an investigation of documentary and comparative data. Data collection considered perceptions of construction practices regarding the circular economy and the specificity of each situation and reflected the actual production systems. We used simple random sampling to collect data in the scope of the study. The findings show the importance of some relational elements between companies that structure construction projects, supporting the impact of discovering specific variables in the different layers of sustainable management. In addition, results show how those responsible for construction projects understand sustainability as a preference, amplify the role of various factors in the work of the cultural and social ecosystems under consideration. Finally, this article details and analyzes the channeling of innovative business models in the fourth sector.
Keywords: business model; Chile; circular economy; construction; environment; fourth sector; sustainability; JCR; Scopus